High-speed C–H chlorination of ethylene carbonate using a new photoflow setup - Kasakado, Takayoshi; Fukuyama, Takahide; Nakagawa, Tomohiro; Taguchi, Shinji; Ryu, Ilhyong (Beilstein Journal of Organic Chemistry, 2022)
We report the high-speed C–H chlorination of ethylene carbonate, which gives chloroethylene carbonate, a precursor to vinylene carbonate. A novel photoflow setup designed for a gas–liquid biphasic reaction turned out to be useful for the direct use of chlorine gas. The setup employed sloped channels so as to make the liquid phase thinner, ensuring a high surface-to-volume ratio. When ethylene carbonate was introduced to the reactor, the residence time was measured to be 15 or 30 s, depending on the slope of the reactor set at 15 or 5°, respectively. Such short time of exposition sufficed the photo C–H chlorination. The partial irradiation of the flow channels also sufficed for the C–H chlorination, which is consistent with the requirement of photoirradiation for the purpose of radical initiation. Near-complete selectivity for single chlorination required the low conversion of ethylene carbonate such as 9%, which was controlled by limited introduction of chlorine gas. At a higher conversion of ethylene carbonate such as 61%, the selectivity for monochlorinated ethylene carbonate over dichlorinated ethylene carbonate was 86%. We found that the substrate contamination with water negatively influenced the performance of the C–H chlorination.
Keywords: C–H chlorination; chlorine gas; ethylene carbonate; photo flow reactor; vinylene carbonate

(untitled) - Ingold, K. U.; Lusztyk, J.; Raner, K. D. (Acc. Chem. Res., 1990)

(untitled) - Fletcher, B.; Suleman, N. K.; Tanko, J. M. (J. Am. Chem. Soc., 1998)

(untitled) - Sun, N.; Klabunde, K. J. (J. Am. Chem. Soc., 1999)

(untitled) - Pease, R. N.; Walz, G. F. (J. Am. Chem. Soc., 1931)

(untitled) - Brown, H. C.; Kharasch, M. S.; Chao, T. H. (J. Am. Chem. Soc., 1940)

(untitled) - Kharasch, M. S.; Berkman, M. G. (J. Org. Chem., 1941)

(untitled) - Wang, Y.; Liu, Y.; Wiley, D.; Zhao, S.; Tang, Z. (J. Mater. Chem. A, 2021)
See for a recent review.

Flash Chemistry: Fast Organic Synthesis in Microsystems - Yoshida, J.-i. (John Wiley & Sons, 2008)

(untitled) - Ehrich, H.; Linke, D.; Morgenschweis, K.; Baerns, M.; Jähnisch, K. (Chimia, 2002)

(untitled) - Matsubara, H.; Hino, Y.; Tokizane, M.; Ryu, I. (Chem. Eng. J., 2011)

(untitled) - Fukuyama, T.; Tokizane, M.; Matsui, A.; Ryu, I. (React. Chem. Eng., 2016)

(untitled) - Strauss, F. J.; Cantillo, D.; Guerra, J.; Kappe, C. O. (React. Chem. Eng., 2016)

(untitled) - Hyodo, M.; Iwano, H.; Kasakado, T.; Fukuyama, T.; Ryu, I. (Micromachines, 2021)

(untitled) - Zhang, S. S. (J. Power Sources, 2006)
See for a review on electrolyte additives for lithium ion batteries.

(untitled) - Ivanov, S.; Sauerteig, D.; Dimitrova, A.; Krischok, S.; Bund, A. (J. Power Sources, 2020)

(untitled) - Michan, A. L.; Parimalam, B. S.; Leskes, M.; Kerber, R. N.; Yoon, T.; Grey, C. P.; Lucht, B. L. (Chem. Mater., 2016)

(untitled) - Liu, Y.-H.; Takeda, S.; Kaneko, I.; Yoshitake, H.; Yanagida, M.; Saito, Y.; Sakai, T. (RSC Adv., 2016)

(untitled) - Wang, Y.; Nakamura, S.; Tasaki, K.; Balbuena, P. B. (J. Am. Chem. Soc., 2002)

(untitled) - Burns, J. C.; Petibon, R.; Nelson, K. J.; Sinha, N. N.; Kassam, A.; Way, B. M.; Dahn, J. R. (J. Electrochem. Soc., 2013)

(untitled) - Xiong, D.; Burns, J. C.; Smith, A. J.; Sinha, N.; Dahn, J. R. (J. Electrochem. Soc., 2011)

(untitled) - Aotake, T.; Tanimoto, H.; Hotta, H.; Kuzuhara, D.; Okujima, T.; Uno, H.; Yamada, H. (Chem. Commun., 2013)

(untitled) - Geiseler, O.; Müller, M.; Podlech, J. (Tetrahedron, 2013)

(untitled) - Revés, M.; Lledó, A.; Ji, Y.; Blasi, E.; Riera, A.; Verdaguer, X. (Org. Lett., 2012)

(untitled) - Dong, S.; Cahill, K. J.; Kang, M.-I.; Colburn, N. H.; Henrich, C. J.; Wilson, J. A.; Beutler, J. A.; Johnson, R. P.; Porco, J. A., Jr (J. Org. Chem., 2011)

(untitled) - Taffin, C.; Kreutler, G.; Bourgeois, D.; Clot, E.; Périgaud, C. (New J. Chem., 2010)

(untitled) - Huang, X.; Wu, J.; Wang, X.; Tian, Y.; Zhang, F.; Yang, M.; Xu, B.; Wu, B.; Liu, X.; Li, H. (ACS Appl. Energy Mater., 2021)

(untitled) - Zhang, Y.; Chen, S.; Chen, Y.; Li, L. (Mater. Chem. Front., 2021)

(untitled) - Li, H.; Yang, J.; Xu, Z.; Lu, H.; Zhang, T.; Chen, S.; Wang, J.; NuLi, Y.; Hirano, S.-i. (ACS Appl. Energy Mater., 2020)

(untitled) - Chai, J.; Liu, Z.; Zhang, J.; Sun, J.; Tian, Z.; Ji, Y.; Tang, K.; Zhou, X.; Cui, G. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Zhao, H.; Zhou, X.; Park, S.-J.; Shi, F.; Fu, Y.; Ling, M.; Yuca, N.; Battaglia, V.; Liu, G. (J. Power Sources, 2014)

(untitled) - Allmand, A. J.; Cunliffe, P. W.; Maddison, R. E. W. (J. Chem. Soc., Trans., 1925)